Neferine, an alkaloid from lotus seed embryo, inhibits human lung cancer cell growth by MAPK activation and cell cycle arrest. (24th August 2013) - Poornima, Paramasivan; Weng, Ching Feng; Padma, Viswanadha Vijaya
Abstract Neferine is the major bisbenzylisoquinoline alkaloid isolated from the seed embryo of a traditional medicinal plant Nelumbo nucifera (Lotus). Epidemiological studies have revealed the therapeutic potential of lotus seed embryo. Although several mechanisms have been proposed, a clear anticancer action mechanism of neferine on lung cancer cells is still not known. Lung cancer is the most common cause of cancer death in the world, and the patients with advanced stage of nonsmall lung cancer require adjunct chemotherapy after surgical resection for the eradication of cancer cells. In this study, the effects of neferine were evaluated and characterized in A549 cells. Neferine induced apoptosis in a dose‐dependent manner with the hypergeneration of reactive oxygen species, activation of MAPKs, lipid peroxidation, depletion of cellular antioxidant pool, loss of mitochondrial membrane potential, and intracellular calcium accumulation. Furthermore, neferine treatment leads to the inhibition of nuclear factor kappaB and Bcl2, upregulation of Bax and Bad, release of cytochrome C, activation of caspase cascade, and DNA fragmentation. In addition, neferine could induce p53 and its effector protein p21 and downregulation of cell cycle regulatory protein cyclin D1 thereby inducing G1 cell cycle arrest. These results suggest a novel function of neferine as an apoptosis inducer in lung cancer cells. © 2013 BioFactors, 40(1):121–131, 2014